The Description of Mathematics Problem Solving Skills Reviewed from The Learning Style in Students of Grade VI of SDN 44 Rampoang Palopo - Hasnah HP (Yayasan Ahmar Cendekia Indonesia, 2022)
This research aimed for the mathematical problem-solving ability of comparative materials reviewed from visual learning styles in classroom students. This research was descriptive research, which seeked to find out and describe the mathematical problem-solving skills of comparative materials in terms of learning styles in classroom students. Processed data was the ability to solve mathematical problems in terms of uditory and visual learning styles. The data collection technique used was in the form of giving questionnaires, writing testers and interviews. The questionnaire used was a statement-shaped questionnaire to analyze each student's learning style, namely visual and auditory, problems used in the test of problem-solving skills in the form of comparative materials, which amount to 2 numbers, and interviews aimed to find out the learning skills of students in solving comparative problems. The validity of the data used was triangulation method. Data analysis techniques are by using data reduction, data presentation, and verification. Based on the processing of the data, it was obtained that subjects with mathematical problem-solving skills based on visual learning styles on SV1 subjects were able to meet all four indicators of problem-solving ability according to Polya's steps, namely understanding problems, drawing plans, implementing plans, and reevaluating.